2018
DOI: 10.1111/jog.13833
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of motherwort injection add‐on therapy to carboprost tromethamine for prevention of post‐partum blood loss: A meta‐analysis of randomized controlled trials

Abstract: Motherwort (YiMuCao), a traditional Chinese herb, has been shown beneficial effects for women's diseases. This meta-analysis aimed to evaluate the efficacy and safety of motherwort injection add-on therapy to carboprost tromethamine for prevention of post-partum blood loss. A systematic literature search was conducted in PubMed, Embase, Cochrane Library, CNKI, VIP and Wanfang from their inception to December 2017. Randomized controlled trials that determined the add-on effects of motherwort injection to carbop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The dose of carboprost tromethamine was 250 μg and the total dose of motherwort injection ranged from 60 to 200 mg. There was no statistically significant difference in the incidence of the most frequently reported adverse events (nausea, vomiting, chest tightness, hypertension, and shivering) between mothers who received carboprost or mortherwort (RR=0.76; 95% CI: 0.50-1.16) 113…”
Section: Herbal Use Postpartummentioning
confidence: 87%
See 1 more Smart Citation
“…The dose of carboprost tromethamine was 250 μg and the total dose of motherwort injection ranged from 60 to 200 mg. There was no statistically significant difference in the incidence of the most frequently reported adverse events (nausea, vomiting, chest tightness, hypertension, and shivering) between mothers who received carboprost or mortherwort (RR=0.76; 95% CI: 0.50-1.16) 113…”
Section: Herbal Use Postpartummentioning
confidence: 87%
“…There was no statistically significant difference in the incidence of the most frequently reported adverse events (nausea, vomiting, chest tightness, hypertension, and shivering) between mothers who received carboprost or mortherwort (RR = 0.76; 95% CI: 0.50-1.16). 113 In 2018, Chen and colleagues performed a systematic review and meta-analysis of randomized controlled trials that compared motherwort injection alone or in combination with oxytocin in pregnant women delivered by cesarean. Forty-six trials involving 7359 delivered women were included.…”
Section: Blood Lossmentioning
confidence: 99%
“…In the past, motherwort was considered as a safe and non-toxic TCM. In recent years, accumulating studies have found that long-term and high-dose use of motherwort will cause some adverse reactions, mainly manifested as sudden feeling of general weakness, paralysis of the lower limbs, severe sweating, decreased blood pressure, and rapid breathing, and even cause uterine contractions and lead to miscarriage in pregnant women [ 36 , 37 ].…”
Section: The Main Tcms For Regulating Ferroptosismentioning
confidence: 99%
“…Meanwhile, increasing evidences have also highlighted the application of Chinese herbal medicine (CHM), including botanical, animal, and mineral agents, in the treatment of cancers, BC, for instance, by virtue of their valuable pharmacological activities with low toxicity (Sun et al., 2016; Zou et al., 2020). Chinese motherwort (YiMuCao, Leonurus japonicus ) is a traditional Chinese herb showing therapeutic effects for obstetrical and gynecological diseases (Meng et al., 2019; Miao et al., 2019). Among the active compounds, Stachydrine has been widely investigated (Shang et al., 2014).…”
Section: Introductionmentioning
confidence: 99%